Effect of Red Betel (Piper crocatum) Leaf Ethanol Extract On Increased Creatinine and Ureum Levels In White Rat Wistar Strain Induced Streptozotosin-Nikotinamid - Navirius, Franz June; Pamudji, Gunawan; Herowati, Rina (Universitas Ahmad Dahlan, 2023)
Red betel (Piper crocatum) is a herbal plant that has various bioactivities including antioxidant activity. Red betel leaf can be used in the treatment of diabetes mellitus and has properties as an antioxidant. This study aims to find the activity of normal levels of creatinine and urea induced by Streptozotosin-Nicotinamide in diabetic rats. Red betel leaves are extracted by soaking in 96% ethanol solvent. Phytochemical screening is used to test the class of compounds in red betel leaf extract using the test tube method. Experimental animals in the study were placed in 6 treatment groups, namely no treatment (CMC 1%), negative control (STZ-NA), positive control (Glibenclamide), dose 1 (125 mg/kg BW), dose 2 (250 mg/kg BW), and dose 3 (500 mg/kg BW). A UV-Vis spectrophotometer was used to measure creatinine and urea on days 24, 31, and 39. One Way ANOVA and Post Hoc Test Multiple Comparisons-Tukey HSD were the data analyzers used. Flavonoids, tannins, saponins and alkaloids were shown from the phytochemical screening. Data analysis showed that the 500 mg/kg BW ethanol extract of red betel leaves was able to produce creatinine and urea better than the 125 mg/kg BW and 250 mg/kg BW ethanol extracts of red betel leaves. This situation is due to red betel leaf extract 500 mg/kg BW Data analysis showed that the 500 mg/kg BW ethanol extract of red betel leaves was able to produce creatinine and urea better than the 125 mg/kg BW and 250 mg/kg BW ethanol extracts of red betel leaves.